Pengelolaan Sarana Dan Prasarana Pendidikan Di Sekolah - Kartini Kartini; Amin Sobar; Karyaningtyas Karyaningtyas (STAI Publisistik Thawalib Jakarta, 2023)
The aim of the research is to explain and describe the management of facilities and infrastructure at the Muhammadiyah 11 Bidaracina elementary school. Research method using qualitative case studies. Collection techniques using interviews, observation, and documentation. Data processing techniques using reduction, data presentation, and conclusions. Data wetness technique with triangulation of sources and techniques. Research results: planning with infrastructure needs analysis through the school principal. Procurement by purchasing planned goods. Use by using the facilities and infrastructure that have been purchased. Maintenance with daily and periodic maintenance. Supervision by controlling every use of school infrastructure.